The impact of credit implied volatility on long term financial investments - Ferreira, Kelly Luiana Sulissa (2020)
The goal of this dissertation is to expose how the short and long term volatilities are different from one another. Volatility is an essential instrument in the financial world, the most frequently used volatility is calculated though the equity market. The volatility calculated this way has a short term perspective, since the equity market is composed, by a large majority, of products with shorter maturities. The worries and priorities of short term investors are very different from the ones of long term investors., therefore they shouldn’t use the same volatility. In order to find the volatility in the long term, the market for credit default swaps (CDS) was used, since it’s mainly composed of swaps with maturities between 5 years and 10 years. By comparing the credit implied volatility with the equity implied volatility. It was possible to conclude that for the same company in the same time period, both volatilities had very different behaviors. The credit implied volatility is less sensitive to changes in the market then the equity implied volatility. Also, the credit implied volatility is higher on companies with higher debt, having stronger reactions on these companies than on the ones which are financially stable.